FORMULATION OF THE PROBLEM OF THE ESTIMATE OF THE EFFECTIVENESS OF COOPERATION OF MILITARY FORCES WITH THE FORCES OF CIVIL PROTECTION IN AT THE LIQUIDATION OF CONSEQUENCES OF EMERGENCIES - Neklonskyi І. М.; Biletskyi, S. V.; Romashchenko О. А. (Honor and Law, 2019)
The problem of the estimate of the effectiveness of cooperation of military forces with the forces of civil protection in at the liquidation of consequences of emergencies through the implementation of a specific variant of the interaction was formulated.